Evaluation of rice grain yield and yield components of Nona Bokra chromosome segment substitution lines with the genetic background of Koshihikari, in a saline paddy field. Issue 5 (13th July 2019) - Mitsuya, Shiro; Murakami, Norifumi; Sato, Tadashi; Kazama, Tomohiko; Toriyama, Kinya; Skoulding, Nicola Stephanie; Kano-Nakata, Mana; Yamauchi, Akira
Abstract: The ability to tolerate salt differs with the growth stages of rice and thus the yield components that are determined during various growth stages, are differentially affected by salt stress. In this study, we utilized chromosome segment substitution lines (CSSLs) from Nona Bokra, a salt-tolerant indica landrace, with the genetic background of Koshihikari, a salt-susceptible japonica variety. These were screened to find superior CSSLs under long-term saline conditions that showed higher grain yield and yield components in comparison to Koshihikari. One-month-old seedlings were transplanted into a paddy field without salinity. These were allowed to establish for 1 month further, then the field was flooded, with saline water maintained at 7.41 dS m −1 salinity until harvest. The experiments were performed twice, once in 2015 and a targeted study in 2016. Salt tolerance of growth and reproductive stage parameters was evaluated as the Salt Effect Index (SEI) which was computed as the difference in each parameter within each line between control and saline conditions. All CSSLs and Koshihikari showed a decrease in grain yield and yield components except panicle number under salinity. SL538 showed a higher SEI for grain yield compared with Koshihikari under salinity throughout the two experiments. This was attributed to the retained grain filling and harvest index, yet the mechanism was not due to maintaining Na +, Cl − and K + homeostasis. Few other CSSLs showed greater SEI for grain weight under salinity compared with Koshihikari, which might be related to low concentration of Na + in leaves and panicles. These data indicate that substitution of different Nona Bokra chromosome segments independently contributed to the maintenance of grain filling and grain weight of Koshihikari under saline conditions. Abstract : We evaluated grain yield and yield components of Nona Bokra chromosome segment substitution lines (CSSLs) with the genetic background of Koshihikari in a saline paddy field. SL538 showed higher grain yield and grain filling than Koshihikari under salinity, which was not attributed to Na +, Cl − and K + homeostasis in this rice genotype. SL501, 502 and 503 maintained grain weight under salinity compared with Koshihikari, which was related to low Na + concentration in leaves and panicles. This study implies the independent genetic control of salt tolerance of each yield component, and this may not always be related to superior salt exclusion ability.